Nanosafety: Validating Metal‐Organic Framework Nanoparticles for Their Nanosafety in Diverse Biomedical Applications (Adv. Healthcare Mater. 2/2017). Issue 2 (January 2017) - Wuttke, Stefan; Zimpel, Andreas; Bein, Thomas; Braig, Simone; Stoiber, Katharina; Vollmar, Angelika; Müller, Dominik; Haastert‐Talini, Kirsten; Schaeske, Jörn; Stiesch, Meike; Zahn, Gesa; Mohmeyer, Alexander; et al.
Abstract : Metal‐organic frameworks (MOFs) are a promising platform for the synthesis of porous nanoparticles for diverse medical applications. Stefan Wuttke, Silke Meiners, and co‐workers comprehensively investigate the nanosafety and hence the general applicability of different MOF nanoparticles for distinct fields of medical applications (e.g. drug delivery or implant coatings) in article 1600818. Data presented here suggest the need to evaluate the nanosafety of each MOF nanomaterial with respect to their particular medical application.